2022
DOI: 10.3389/fmars.2022.956848
|View full text |Cite
|
Sign up to set email alerts
|

Lionfish on the loose: Pterois invade shallow habitats in the tropical southwestern Atlantic

Abstract: Lionfish (Pterois spp.) evolved in the Indo-Pacific with predators and prey and invaded regions (e.g., the Caribbean Sea and Mediterranean) where no such balance yet exists. In 2020, four lionfish were recorded on mesophotic reefs of the Amazon offshore Coast and Fernando de Noronha Archipelago. However, until now, there were no records of invasive lionfish in Brazilian nearshore waters or even such a high number of individuals. In this article, we report the continuing invasion process along the Brazilian Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
1
15
0
5
Order By: Relevance
“…The presence of lionfish in shallow waters (< 15 m) in fishing traps, and estuarine habitats indicates fast adaptation e spread condition for the species (SOARES et al, 2022). In our study, fish caught near piping of the inlet pump of a shrimp larviculture call attention for fish movement on different habitats and or that could be accidentally enter inside channel due to bombs water pressure.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The presence of lionfish in shallow waters (< 15 m) in fishing traps, and estuarine habitats indicates fast adaptation e spread condition for the species (SOARES et al, 2022). In our study, fish caught near piping of the inlet pump of a shrimp larviculture call attention for fish movement on different habitats and or that could be accidentally enter inside channel due to bombs water pressure.…”
Section: Discussionmentioning
confidence: 67%
“…Higher number of individuals were registered in Fernando de Noronha Island, indicating possible population establishment (LUIZ et al, 2021). Soares et al (2022) presents the first record for lionfish in Piauí and Ceará states, northeastern Brazil in shallow water (< 15 m), and hypothesizes fish spread from F. Noronha Island throughout North Brazilian Current. Although, previous reports contributed for the comprehension of distribution and habitat use from lionfish invasion, presence of the species in estuarine and nearshore habitats on this study contributes for new knowledge about tolerance and adaptation of its species.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Cintra et al (2022c) andSoares et al (2022), reported the presence of the lion sh in Brazilian shallow waters, with depths ranging from 1 to 10 meters.Studies provided byMorris-Jr. (2009) indicated the high reproductive rate of the lion sh in North and South Carolina waters and in the Bahamas; they report the high egg production (~ two millions of eggs per year), which gives lion sh the high capacity of colonization of new habitats. Some biological characteristics indicate the risk of this introduction into brazilian waters such as: 1) the individuals can reach the sexual maturity at one year of age; 2) fty percent of the males of lion sh were observed in sexual maturity around ~ 100 mm of total length (TL), while the females were observed in sexual is urgent to provide environmental education for the community, as well as information to avoid accidents with the population on the beaches, which incidents with humans ( shermen and bathers) in Brazil have been reported by Haddad Junior et al(2022).…”
mentioning
confidence: 99%